Geographic variation in ectoparasitic mites diversity in Tadarida Brasiliensis (Chiroptera, Molossidae) - Pesenti,Tatiana C. (2014)
Tadarida brasiliensis (Geoffroy, 1824), the Brazilian free-tailed bat, is an insectivorous bat that occurs from southern United States of America to southern South America. In this study we present the first data on diversity of ectoparasitic mites of T. brasiliensis in Brazil. A compilation and analysis of the studies of mite diversity conducted in different points the geographic distribution this bat species are provided. The mites were collected from March 2010 to November 2011 on 160 T. brasiliensis adult bats captured in southern Brazil. Four species of mites have been found: Chiroptonyssus robustipes (Ewing, 1925), Ewingana longa (Ewing, 1938), Ewingana inaequalis (Radford, 1948), and specimens of Cheyletidae. Chiroptonyssus robustipes was the most prevalent species (100%), followed by E. longa (20%), E. inaequalis (10%), and specimens of Cheyletidae (1.25%). The data currently available show that C. robustipes parasitizes T. brasiliensis throughout its region of occurrence, and this mite is highly prevalent and abundant. The two species of Ewingana accompany the geographical distribution of T. brasiliensis, but with much lower prevalence and abundance.